Research Grant Decision Support System Based on The PROMETHEE II Method - Alwendi Alwendi; Andi Saputra Mandopa (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2023)
Community Service (P2M) is a form of lecturer activity in contributing directly to the community. To support lecturers in the implementation is the Internal Service Grant Program. The Internal Grant Service Program is intended as a service activity in the context of fostering and directing lecturers to improve their ability in community service. The purpose of this study is to apply the Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE II) in the case of Lecturers Receiving Internal Service Grants. Assessment of P2M Grant proposals is still manual without a system to assist reviewers. To overcome these problems a Decision Support System (SPK) is needed which is expected to resolve the problem in granting an internal P2M Grant. Comparative analysis is only done to maintain the quality of community service at Graha Nusantara University, Padangsidimpuan. The application of the Promethee II method is expected to help reviewers in determining the prospective lecturers receiving the P2M Internal Grant